Do perioperative antibiotics reduce the risk of surgical‐site infections following excision of ulcerated skin cancers? A Critically Appraised Topic. (18th January 2018) - Chan, S.A.; Wernham, A.G.H.; Stembridge, N.; Harper, N.; Verykiou, S.; Fremlin, G.A.; Abbott, R.A.; Matin, R.N.
Summary: Aim: To review the efficacy of perioperative antibiotics in reducing the risk of surgical‐site infections (SSIs) following excision of ulcerated skin cancers. Setting and design: Study selection, data extraction and analysis were carried out independently by four authors. Only randomized controlled trials (RCTs) reported in the English language were included. Included studies: RCTs in the English language in which patients received perioperative topical, intralesional or oral antibiotics for dermatological surgery, including Mohs micrographic surgery in general practice, dermatology or plastic surgery departments, were included. Outcome: The proportion of participants developing SSI following excision of skin lesions. Results: Thirteen RCTs were identified from our literature search of PubMed and Embase, which evaluated SSI following use of topical ( n  = 5), oral ( n  = 3), intramuscular ( n  = 2), intravenous ( n  = 1) and intralesional antibiotics ( n  = 2) in dermatological surgery. Two RCTs specifically investigated SSIs in ulcerated skin cancer excisions; one RCT investigated the SSI rate following surgical treatment specifically for ulcerated skin cancers in individuals randomized to topical antibiotics vs. oral cephalexin; and one RCT compared intravenous cefazolin with no antibiotic, demonstrating significant reduction in SSI rates for ulcerated tumours ( P  = 0·04). Conclusions: The heterogeneity of the RCTs included in this study makes it difficult to make a direct comparison of the outcomes measured. High‐quality evidence demonstrating a beneficial effect of the use of perioperative antibiotics to prevent SSI following excision of ulcerated skin cancers is lacking. In the absence of an evidence base, we propose that a well‐designed multicentre RCT could evaluate the effect of perioperative antibiotics following excision of ulcerated tumours, and potentially reduce inappropriate antibiotic prescription. Abstract : Plain language summary available online